Need, merit, and politics in multilateral aid allocation: A district-level analysis of World Bank projects in India - Peter Nunnenkamp; Hannes Öhler; Maximiliano Sosa Andrés (Kiel Institute for the World Economy (IfW), 2012)
The targeting of foreign aid within recipient countries is largely unexplored territory. We help close this gap in empirical research on aid allocation by employing Poisson estimations on the determinants of the World Bank's choice of project locations at the district level in India. The evidence of needs-based location choices is very weak, even though World Bank activities tend to concentrate in relatively remote districts. Spatial lags prove to be significant and positive pointing to regional clustering. Institutional conditions matter insofar as project locations cluster in districts belonging to states with greater openness to trade. We do not find any evidence that location choices are affected by political patronage at the state or district level. However, the World Bank prefers districts where foreign direct investors may benefit from projects related to infrastructure.
Keywords: F35; F53; 330; Aid allocation; World Bank; Indian districts; Political constituency; Entwicklungshilfe; Entwicklungsprojekt; Regionales Cluster; Standortfaktor; Infrastrukturbedarf; Direktinvestition; Public Choice; Welt; Indien